(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Easy availability and reduced side effects of plants and plant-derived herbal preparations are the gifts of nature and are useful since ancient time for the treatment of various diseases. From this view point twoBangladeshi plants, Uraria lagopodies DC. and Urena lobata L. have been evaluated for their possible pharmacological activities. Preliminary phytochemical screenings with the crude ethanol extracts demonstrated the presence of alkaloids, glycosides, tannins, saponins, steroids and reducing sugars. The crude extract of U. lagopodies significantly (p<0.001) increased the charcoal evacuation by 375 min at 500 mg/kg body weight of mice when compared to the standard, Loperamide by 391.8 min at 5 mg/kg b.w. In the acetic acid induced analgesic activity test, the oral administration of ethanol extract of U. lobata produced significant (p<0.05) pain relieving activity (number of writhing 32) at 500 mg/kg body weight as compared to standard diclofenac-Na. Both the crude extracts showed mild anti-inflammatory and membrane stabilizing activities during the heat induced anti-inflammatory test and membrane stabilization screening. A dose dependent biological activity was observed during the study period. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12490 Dhaka Univ. J. Pharm. Sci. 11(1): 65-69, 2012 (June)